Awareness and consequences of human immuno deficiency virus disease among undergraduate students of university of Illorin (2015)
The study examined awareness and consequences of human immune deficiency virus disease among undergraduate students of University of Ilorin. Four research hypotheses were postulated and tested at 0.05 alpha level. The research design adopted for the study was survey type. Through simple random technique, five (5) departments were selected and a sampled size of four hundred and twenty was drawn from selected departments with the use of stratified sampling technique in the University of Ilorin, Kwara State. Data were collected with the use of researcher’s structured questionnaire already validated by the three experts in the field of Human Sexuality, Health Education and Sociology and tested with the use of test re-test reliability technique. A reliability coefficient of .75r was obtained. Demographic data collected were analyzed with the aid of frequency count and simple percentage while the postulated hypotheses were tested with the use of inferential statistics of Chi-square. The result of the study revealed that undergraduate students are significantly different in their awareness on causes, transmission routes, consequences and control of HIV/AIDS. Based on these findings, the researcher recommended that undergraduate students should abstain from indiscriminate sex, it is also recommended that HIV/AIDS education should be carried out by professional concerned in the universities.